Technical Efficiency and Farmer Decision-Making in Integrated Rice-Fish Farming in Flood-Prone Areas: A Case Study of Pasuruan Regency, East Java - Mamilianti, Wenny; Saifuddin, Ary Bunayya; Pramadani, Kelvin Angga; Samudro, Kresno Aji Bayu (Faculty of Fisheries and Marine Science, Brawijaya University, 2026)
Flooding occurs almost annually in Kedungboto Village, Pasuruan Regency, Indonesia, restricting farmers to a single rice-growing season due to prolonged field inundation. As an adaptive strategy, some farmers integrate fish farming during the rainy season; however, its contribution to farm efficiency remains insufficiently examined. This study aims to evaluate the technical efficiency of rice farming in flood-prone areas and to analyze the factors influencing farmers decisions to adopt rice-fish farming systems. A total of 120 farmers were surveyed, comprising 60 rice-fish farmers and 60 rice-only farmers. Technical efficiency was measured using Data Envelopment Analysis (DEA), while logistic regression was employed to identify the determinants of adoption. The results indicate that rice-fish farmers achieve higher average technical efficiency (0.82) than rice-only farmers (0.67). Technical efficiency, landholding size, farm income, knowledge of fish farming, and access to freshwater fish markets significantly influence adoption decisions. An odds ratio of 1.054 suggests that higher technical efficiency increases the likelihood of adopting rice-fish systems. These findings highlight the role of rice-fish integration in enhancing farm performance and resilience. Strengthening extension services and improving flood control infrastructure are essential to support sustainable and wider adoption.